2015
DOI: 10.2399/ana.15.008
|View full text |Cite
|
Sign up to set email alerts
|

Unusual origin of three headed biceps brachii muscle

Abstract: The biceps brachii is one of the most variable muscles in the human body in terms of the number of heads contributing to the muscle. The most common origin of these supernumerary heads is along the humeral shaft. We document a previously unreported point of origin for a supernumerary head. Routine dissection of a 10% formalin fixed upper extremity of a 72 year old Caucasian male, revealed a tricipital biceps brachii muscle. The third head took its origin from the deep investing fascia of the brachialis muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…En estudios por imágenes o incluso durante actos quirúrgi-cos pueden ser confundidos con tumores de partes blandas. Pueden ocasionar desplazamientos inesperados en fracturas de húmero (Nakatani et al, 1998;Rodríguez-Niedenführ et al;Reilly & Kamineni;Jayasudha et al, 2013;LutterbachPenna et al).…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…En estudios por imágenes o incluso durante actos quirúrgi-cos pueden ser confundidos con tumores de partes blandas. Pueden ocasionar desplazamientos inesperados en fracturas de húmero (Nakatani et al, 1998;Rodríguez-Niedenführ et al;Reilly & Kamineni;Jayasudha et al, 2013;LutterbachPenna et al).…”
Section: Resultados Y Discusiónunclassified
“…Se origina en dos cabezas que toman inserción en la escápula; su porción interna o cabeza corta a nivel del vértice del proceso coracoides mientras que su porción externa o cabeza larga en el tubérculo proximal a la articulación del codo. Este tendón terminal, que presenta fibras anteriores procedentes de la cabeza corta y posteriores procedentes a su vez de la cabeza larga, se inserta en la tuberosidad del radio, presentando generalmente una expansión aponeurótica que se ensancha en abanico para terminar confundiéndose con la aponeurosis antebraquial que cubre a los músculos epitrocleares, que a su vez se inserta en el margen posterior de la ulna (Testut & Latarjet, 1984;Pakhale et al ., 2012; Pró, 2012;Sawant, 2013;Reilly & Kamineni, 2015).El miembro superior presenta múltiples variaciones anatómicas, tanto musculares como vasculonerviosas. El músculo bíceps braquial está sujeto a múltiples variaciones, siendo considerado como uno de los músculos que más variaciones presenta, sobre todo en cuanto al número y morfología de sus cabezas (Rodríguez-Niedenführ et al ., 2003;Ilayperuma et al, 2011).…”
unclassified
“…The biceps brachii is a dominant muscle of the anterior compartment of the arm and is characteristically illustrated as a large, fusiform muscle with two heads. [ 1 ] The short head originates from the tip of the coracoid process, and the intracapsular tendon of long head arises from the supraglenoid tubercle of the scapula. The two tendons lead into closely applied elongated bellies to terminate in a flattened tendon about 7 cm from elbow joint and get inserted into the rough posterior area of the radial tuberosity The tendon gives a broad medial expansion, the bicipital aponeurosis, which merges with the antebrachial fascia.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of the supernumerary head of the biceps brachii is also often coupled with variations of MCN which may incorporate a peculiar branching pattern, the absence of the nerve or its duplication. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%
“…Musculocutaneous nerve (MCN) supplied all three heads of biceps brachii. Reilly et al 2015 9 first reported of a third head of the biceps solely originating from the fascia of the brachialis muscle. Moreover, the supernumerary heads may confuse a surgeon during shoulder operations and such variations, if unilateral, can be a cause of asymmetry between the two arms and hence, can be confused with pathological conditions such as tumours (Sargon MF et al 1996 3 ).To our knowledge, this is the first report of a third head of the biceps brachii solely originating from under surface of pectoralis major close to its insertion.…”
Section: Observationmentioning
confidence: 99%